Educational stages of industrial and interior design - Salakhidinov Masuddin Sadriddinovich (Genius Journals, 2023)
Interior renovation process has a complex structure due to its intrinsic conditions, the necessity of different sub-contractors’ working together and the high number of components as regards manufacturing. It is extremely important to establish the relationship between cost and design in management of this process correctly. This article discusses about educational stages of industrial and interior design
Keywords: Designs; industrial design; interior design; artistic field; innovation